Transformative Policies and Infrastructure Strengthening Towards the Police Era 4.0 - Supriyanto, Eko Eddya; Rachmawati, Meida; Nugroho, Fibry Jati (Research and Development Agency Ministry of Home Affairs, 2021)
Police transformation policy to carry out community security functions is very adaptive in addressing the changing times. The research aims to map the transformation and strengthening of police infrastructure in response to the era of digitalization. The research uses a qualitative type of research with a literature study approach and policy analysis programmed by the Police. The results showed that the transformation policy consisting of organizational transformation, operation transformation, public service transformation, and supervise transformation is needed by the Police, especially in the current digital transition. Moreover, it can be carried out correctly if the Police have internally and externally owned by POLRI. The research concludes that transformative efforts and strengthening of police infrastructure strongly support the duties and functions of the National Police in securing the community.